2015
DOI: 10.1523/jneurosci.0260-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

ApoE4 and Aβ Oligomers Reduce BDNF Expression via HDAC Nuclear Translocation

Abstract: Apolipoprotein E4 (ApoE4) is a major genetic risk factor for several neurodegenerative disorders, including Alzheimer's disease (AD). Epigenetic dysregulation, including aberrations in histone acetylation, is also associated with AD. We show here for the first time that ApoE4 increases nuclear translocation of histone deacetylases (HDACs) in human neurons, thereby reducing BDNF expression, whereas ApoE3 increases histone 3 acetylation and upregulates BDNF expression. Amyloid-β (Aβ) oligomers, which have been i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(99 citation statements)
references
References 76 publications
(37 reference statements)
6
93
0
Order By: Relevance
“…HuD increases as a result of PKC⑀ activation after learning (67) and stabilizes the mRNA for BDNF, nerve growth factor (NGF), and neurotrophin-3 (NT-3) (19). PKC⑀ activation induces the synthesis of BDNF (10,20,47), and BDNF induces transport of PSD-95 to the dendrites (68), which is required for maintenance of mature spines (69). Deficits of PKC⑀ function could also contribute to the synapse loss in Alzheimer disease (15), whereas the therapeutic elimination of such deficits may offer a strategy for the treatment of synaptic loss in Alzheimer disease and other synaptic disorders.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HuD increases as a result of PKC⑀ activation after learning (67) and stabilizes the mRNA for BDNF, nerve growth factor (NGF), and neurotrophin-3 (NT-3) (19). PKC⑀ activation induces the synthesis of BDNF (10,20,47), and BDNF induces transport of PSD-95 to the dendrites (68), which is required for maintenance of mature spines (69). Deficits of PKC⑀ function could also contribute to the synapse loss in Alzheimer disease (15), whereas the therapeutic elimination of such deficits may offer a strategy for the treatment of synaptic loss in Alzheimer disease and other synaptic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…PKC activation induces protein synthesis required for long term memory (12,18). PKC⑀ activation is also required for HuD-mediated mRNA stabilization of neurotrophic factors (19) and apoE-mediated epigenetic regulation of BDNF (20). PKC activation induces translocation of calcium/ calmodulin-dependent kinase II (CaMKII) 2 to synapses (21) where it participates in PSD-95-induced synaptic strengthening (22).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings also involved changes in HDAC 4 and HDAC 6 nuclear localization that depend on the AD genetic risk factor APOE 4 (86). APOE ε4 increases by a 2-3 fold chance to develop early onset of AD when it is represented as a single allele and by over 12-fold when two APOE ε4 alleles are expressed.…”
Section: A Multifactorial Disease: Alzheimer's Disease (Ad)mentioning
confidence: 97%
“…Alternatively, a disruption of BDNF signaling would likely reduce or prevent XBP1-dependent amelioration of AD-like pathology (19). In vivo and in vitro studies have demonstrated that oligomeric Aβ alters BDNF expression/function by downregulating its transcripts or impairing axonal transport, with subsequent adverse effects (159)(160)(161)(162)(163)(164)(165). Oligomeric Aβ also reduces BDNF secretion by dendritic cells in humans, thereby decreasing neurotrophic supports for neurons and causing brain damage (166).…”
Section: Potential Mediators Of Xbp1 Signaling In Neuronsmentioning
confidence: 99%